Flexible wearable hybrid nanogenerator to harvest solar energy and human kinetic energy. (1st December 2022) - Kang, Xilong; Jia, Shuhai; Lin, Zihan; Zhang, Huajian; Wang, Longning; Zhou, Xing
Abstract: Solar energy is a clean energy and it is ubiquitous. The movement of people will generate kinetic energy and happened at any time. If solar energy and human kinetic energy could be harvest at the same time, it will be of great significance. In this paper, we used CNTs to fabricate a solar-thermal structure with special concave surface. The solar-thermal conversion ability of this solar-thermal structure is 14.3% higher than other CNTs surface. One side electrode of the pyroelectric nanogenerator was replaced with multi-strip conductive mesh, which can not only conduct electricity, but also cut the magnetic induction line many times to generate electricity. A compact hybrid nanogenerator was fabricated, the thickness is only 410 µm and the density is only 0.065 g/cm 2 . The hybrid nanogenerator is very light and thin, so it is very suitable for people wear. Experiments show that the output power density of hybrid nanogenerator can reach 2.78 mW/m 2 . When participants worn the hybrid nanogenerator during walking and running, it can harvest solar energy and human kinetic energy at the same time. The obtained electrical energy can drive a hygrothermograph to work. In a word, a flexible wearable hybrid nanogenerator to harvest solar energy and human kinetic energy is presented in this paper. This hybrid nanogenerator is suitable for people to wear during outdoor sports, and can realize power supply for outdoor electronic devices. Graphical Abstract: Solar energy is a clean energy and it is ubiquitous. The movement of people will generate kinetic energy and happened at any time. If solar energy and human kinetic energy could be harvest at the same time, it will be of great significance. In this paper, we used CNTs to fabricate a solar-thermal structure with special concave surface. The solar-thermal conversion ability of this solar-thermal structure is 14.3% higher than other CNTs surface. A compact hybrid nanogenerator was fabricated, the thickness is only 410 µm and the density is only 0.065 g/cm 2 . The hybrid nanogenerator is very light and thin, so it is very suitable for people wear. Experiments show that the output power density of hybrid nanogenerator can reach 2.78 mW/m 2 . When participants worn the hybrid nanogenerator during walking and running, it can harvest solar energy and human kinetic energy at the same time. ga1 Highlights: A solar-thermal structure with a special concave surface was fabricated using CNTs. A compact, light and thin hybrid nanogenerator was constructed, which is very suitable for human wear. The hybrid nanogenerator can be used for human wearing, and can harvest solar energy and human kinetic energy at the same time.